Fruit Development in Ficus carica L.: Morphological and Genetic Approaches to Fig Buds for an Evolution From Monoecy Toward Dioecy - Marcotuli, Ilaria; Mazzeo, Andrea; Colasuonno, Pasqualina; Terzano, Roberto; Nigro, Domenica; Porfido, Carlo; Tarantino, Annalisa; Aiese Cigliano, Riccardo; Sanseverino, Walter; Gadaleta, Agata; Ferrara, Giuseppe (Frontiers in Plant Science, 2020)
The mechanism behind the bud evolution towards breba or main crop in Ficus carica L. has not yet been clarified. For this reason, we carried out a combined research by using anatomical, X-ray imaging and genetic techniques. The RNA seq together with structural genome annotation allowed the prediction of 34,629 known genes and 938 novel protein-coding genes. Transcriptome analysis of genes during bud differentiation revealed differentially expressed genes both in two varieties (Dottato and Petrelli) in breba and main crop. The buds of two fig varieties, either requiring or not-requiring pollination to set fruits, were observed under optical microscope and using 3D X-ray tomography, highlighting differences mainly related to the stage of development. The X-ray images of buds showed a great structural similarity between breba and main crop during the initial stages of development. Analysis at the microscope indicated that inflorescence differentiation of breba was split in two seasons whereas that of main crop started at the end of winter of season 2 and was completed within 2-3 months. Gibberellin and auxin biosynthesis genes were more expressed in breba whereas ABA and ethylene in main crop.